The Effect of Plant Growth Regulators on Secondary Metabolite Production in Coriandrum sativum L. - Pathania, Kirti (Thapar Institute of Engineering and Technology, 2025)
The present study was undertaken to investigate the effect of PGRs (BAP and IBA) and elicitor (MeJA) on the in vitro production of secondary metabolites in C. sativum L. (Royal Bliss variety). Seeds were first cultured on basal MS medium for germination. Subsequently, the in vitro plantlets were transferred to MS medium containing different concentrations of BAP (0.0, 1.0, 2.5, 5.0, 10.0 µM) and IBA (0.0, 1.0, 2.5, 5.0, 10.0 µM). Morphological observations showed that the highest shoot multiplication and shoot length occurred on MS medium supplemented with 5.0 μM BAP, while 5.0 μM IBA resulted in the maximum number of roots per explant. Combining these regulators with MeJA revealed differential effects. Although 5.0 μM IBA + 50 μM MeJA inhibited root and shoot formation, it significantly enhanced the production of secondary metabolites, making it the most effective elicitor combination in this study. After sufficient growth, plantlets were harvested, and untargeted metabolite profiling was performed using Gas Chromatography-Mass Spectrometry (GC-MS). GC-MS analysis identified numerous bioactive compounds, and MetaboAnalyst 6.0 with KEGG pathway enrichment analysis was used to determine the affected biosynthetic pathways. Results showed that fatty acid biosynthesis was markedly enhanced under MS + IBA treatment, indicating a strong influence on lipid metabolism. Cutin, suberine, and wax biosynthesis pathways were significantly enriched in MS + BAP and IBA + MeJA treatments, suggesting stress-induced cuticle thickening and volatile compound release. Moreover, phenylacetic acid levels were particularly elevated in MS + 5.0 μM BAP-treated plantlets, pointing to possible modulation of auxin-related pathways. 5.0 μM IBA + 50.0 μM MeJA treatment consistently resulted in the highest diversity and quantity of secondary metabolites, including benzylic alcohols, retinoids, and other aromatic compounds. In conclusion, this study demonstrates that the application of PGRs, particularly in combination with MeJA, can significantly enhance secondary metabolite biosynthesis in coriander. The findings provide new insights into the interaction between PGR treatments and metabolic regulation, offering promising strategies for enhancing secondary metabolite composition in medicinal plants.
Keywords: Coriandrum sativum L; Metabolite Production; Plant Growth Regulator; GC-MS; Sativum L.